A Study on Identifying Mutual Fund as an asset class for Alternative Investment with special reference to Mutual Fund amongst Generation Z - Dukhande, Dr. Priyanka; Shah, Dr. Rahul; Chakravarty, Dr. Kavita (The journal of contemporary issues in business and government, 2022)
The word Savings and Investments are interchangeable in nature which plays an utmost importance in every person’s life. Savings on one hand is to put money safely in a bank account while investing on other hand is to create a gradual increase in the wealth. There are various types of investment avenues available in India. People across various generations depending upon their objectives invest their money into various avenues available. Generation Z who are from mid 1990 to 2010 are the targeted population undertaken in this study. The study is an attempt to understand the awareness and the perception level of Generation Z population towards mutual funds as an investment objective. The sample chosen were from Mumbai city using simple random as the sampling technique. The three major variables studied were risk, returns and liquidity with respect to awareness and perception. The data was analyzed using regression and ANOVA technique. The study showed the investment pattern dependency was more on liquidity.